Full-mouth disinfection as a nonsurgical treatment approach for drug-induced gingival overgrowth: a series of 11 cases - Dannewitz, Bettina; Krieger, Jörg; Simon, Isabel; Dreyhaupt, Jens; Staehle, Hans Jörg; Eickholz, Peter (The international journal of periodontics & restorative dentistry, 2010)
The treatment of drug-induced gingival overgrowth is compounded by the high recurrence rate resulting from chronic use of the medication and the persistence of other risk factors. In this case series, the treatment outcome of a nonsurgical periodontal therapy, according to the concept of full-mouth disinfection in 11 patients with drug-induced gingival overgrowth, is described. All clinical parameters improved significantly after therapy. Only 6% of teeth received further surgical treatment. The clinical situation remained stable during the recall. The present case series suggests that full-mouth disinfection might be a beneficial treatment concept for drug-induced gingival overgrowth, reducing the need for further surgical intervention.